A note on the unique solvability of a class of nonlinear equations - Rabindranath Sen; Sulekha Mukherjee (International Journal of Mathematics and Mathematical Sciences)
The aim of the present note is to devise a simple criterion for the existence of the unique solution of a class of nonlinear equations whose solvability is taken for granted.